Islamic Moderation and Jihad: Insights From Nasr Hamid Abu Zayd and Sahiron Syamsuddin on Qur'an 29:69 - aulya, Tsaqifa; Syaikhah Mumtaz, Ghina (Pusat Kajian Moderasi Beragama dan Ideologi Pancasila UIN Sulthan Thaha Saifuddin Jambi, 2024)
The verses of the Qur'an interpreted by the mufassirscontinue to develop. This is done to achieve the goal of the Qur'anwhich is ṣholi ḥ li kulli zaman wa makan. It is not surprising that themethods of interpreting the Qur'an are very diverse in order to obtainvariations in the meaning of the Qur'an in an integrative manner.This study focuses on the meaning of Jihad contained in the surah alAnkabut / 29: 69. This study discusses the interpretation of twohermeneutical figures, Sahiron Syamsuddin and Nasr Hamid AbuZayd. The questions to be studied are how do the two figures think ininterpreting the verses of jihad and how is the correlation betweenthe hermeneutical interpretation of the verses of jihad andWasathiyah Islam? The method used is the comparative method,with a combined approach between phenomenology and criticaldiscourse analysis. The results of this study reveal that both figuresdeny the existence of textual interpretations of the verses of jihad thatare only related to the context of warfare. According to Syamsuddin,the meaning of jihad in Surah al-Ankabut/29:69 can be seen in threestages: first, jihad against one's own lusts. Second, jihad against thoseclosest to us. Third, jihad against the government, state, andhomeland. Meanwhile, Zayd through his hermeneutics (tafsir alsiyaqi) explains that the meaning of jihad in Surah al-Ankabut/29:69is to free the state from all its problems. The conclusions of the twofigures are relevant to the discourse of Islamic wasathiyyah, because they offer an inclusive, contextual, and relevant perspective on theverses of jihad, so that they are able to answer the challenges of themodern world, including issues such as radicalism, global injustice,and strengthening current humanitarian values.